AL-MAFâÅªLÄT DALAM BAHASA ARAB - , Najihatul Mumtahanah, Prof. Dr. Syamsul Hadi, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is a research concerns of al-mafâÅ«lÄt in Arabic. A research which has accentuated to al-mafâÅ«lÄt concepts and al-mafâÅ«lÄt syntax construction in Arabic, also its function and role in the sentence. In this case, syntax approach has been used to analyze al-mafâÅ«lÄt syntax construction in Arabic, itâs function and role in the structure of Arabic sentence. In the step of analyzing, this research used distributional method to analyze the structure and unit of syntax according to itâs unit and influence. This research concludes several main points, first, al-mafâÅ«lÄt in Arabic has two different concepts, both are as the object of transitive verb, and also as the adverb which explain its regent, the first concept has been defined in al-mafâÅ«l bih while the second is al-mafâÅ«l al-muthlaq (cognate accusative), al-mafâÅ«l li ajlih (causative object), al-mafâÅ«l maâah (adverb of accompaniment), and al-mafâÅ«l fÄ«h (adverb of time and place). Second, al-mafâÅ«lÄt stand on every units of syntax such as word, phrase, and clause. The place of al-mafâÅ«lÄt isnât always placed after its regent, sometime it placed after itâs subject or before itâs predicate. Third, adverb in Arabic that difined in al-mafâÅ«lÄt has different and various roles, such as the emphasize explanation, the explanation of quality and quantity of verb, explanation of aim and purpose of itâs regent, and also the explalnation of time and place of verb.